Spatiotemporal Characteristics of Lateral Reactive Stepping in Individuals with Chronic Stroke. Issue 6 (2nd November 2022) - Tashiro, Hideyuki; Sato, Yui; Fukumoto, Kanta; Toki, Megumi; Kozuka, Naoki
Abstract: We compared the spatiotemporal characteristics of lateral perturbation-induced reactive stepping in stroke subjects with those of age-matched controls. We subjected 12 stroke subjects and 17 healthy elderly controls to lateral stepping. We analyzed first-step spatiotemporal parameters during stepping and recorded the selected reactive step types at the stepping threshold. Stroke subjects showed a lower stepping threshold and more frequently used medial steps than controls. Stroke subjects also had a longer delay prior to foot-off in lateral steps when perturbed toward the nonparetic side, and in medial steps when perturbed toward both sides than controls. Thus, the time deficits in reactive stepping in individuals with stroke may be attributed to stroke-related sensorimotor impairments, indicating their limitations in balance control.